2016
DOI: 10.1016/j.vph.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Nature and nurture in atherosclerosis: The roles of acylcarnitine and cell membrane-fatty acid intermediates

Abstract: Macrophages recycle components of dead cells, including cell membranes. When quantities of lipids from cell membranes of dead cells exceed processing capacity, phospholipid and cholesterol debris accumulate as atheromas. Plasma lipid profiles, particularly HDL and LDL cholesterol, are important tools to monitor atherosclerosis risk. Membrane lipids are exported, as triglycerides or phospholipids, or as cholesterol or cholesterol esters, via lipoproteins for disposal, for re-use in cell membranes, or for fat st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 62 publications
(77 reference statements)
0
12
0
Order By: Relevance
“…23 The significantly lower ratio of free carnitine/acylated carnitine (C0/AC) in COPD patients, despite the lack of distinct differences in the concentration of free carnitine, and the total and individual acylcarnitine levels, possibly indicates a predisposition to atherosclerosis as a result of inadequate β-oxidation of fatty acids, as well as of being at risk for carnitine deficiency. 24,25 Evidence suggests that impaired fatty acid oxidation has some effect on the development of type-2 diabetes. 26,27 The prevalence of diabetes in COPD patients is significant, and may be one of the factors which cause the progression and worsen the prognosis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…23 The significantly lower ratio of free carnitine/acylated carnitine (C0/AC) in COPD patients, despite the lack of distinct differences in the concentration of free carnitine, and the total and individual acylcarnitine levels, possibly indicates a predisposition to atherosclerosis as a result of inadequate β-oxidation of fatty acids, as well as of being at risk for carnitine deficiency. 24,25 Evidence suggests that impaired fatty acid oxidation has some effect on the development of type-2 diabetes. 26,27 The prevalence of diabetes in COPD patients is significant, and may be one of the factors which cause the progression and worsen the prognosis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the accumulation of acylcarnitines, especially those of medium-chain species, has been attributed to incomplete fatty acid oxidation and energy metabolism in CHD 51 . Studies have also suggested the elevation of acylcarnitines as being a signature for inadequate β-oxidation in macrophage lipid metabolism 52 , which is a key process underlying atherosclerosis. Moreover, L-carnitine and acylcarnitines have been shown to contribute to the development of atherosclerosis by increasing the levels of the independent CHD risk factor trimethylamine N-oxide (TMAO) in experimental animals 53 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that alterations in the diet can affect the distribution and chemical composition of plasma lipoproteins in models such as in humans (Blair et al., ), and in animal models such as rabbits (Niimi et al., ), rats (Sawale et al., ), swine (Nichols et al., ) and chickens (Jensen et al., ). Also, it has been shown that the degree of saturation of dietary lipids can affect the chemical composition of plasma lipoproteins in steers (Scislowski et al., ,b) and dairy cows (Offer et al., ).…”
Section: Introductionmentioning
confidence: 99%